The Effect of Personal Factors on the Customer Rating of the Quality of Services of the Islamic Banks Operating in the Syrian Coast - Bittar, Mona L (International Journal of Business, Economics and Management, 2017)
This research aims at identifying with the customers’ evaluation of the quality of services in Islamic banks branches in the Syrian coast (the cities of Latakia and Tartous). As well as knowing the impact of personal factors (gender, age, scientific qualification, income, name of the bank) on this Assessment. In order to achieve this objective, data were collected through a questionnaire designed by Jabnoun and Khalifa (2005). Descriptive statistics has been used to determine the level of the assessment. In order to find out the impact of personal factors on the evaluation & services quality, the analysis of variance test, “Anova test”, has been used. The research found that the customers’ evaluation of services in the studied branches was average in general, and there is no statistically significant impact of the personal variables on the customers’ evaluation of the quality of the studied branches.